Professional psychological qualities of Chinese medical students: theoretical models, questionnaire development, and relationship with mental health - Luo, Wenping; Fan, Wenshu; Xia, Yanglin; Dou, Yanchun; Du, Juan (Frontiers in Psychology, 2024)
The professional psychological qualities encompass essential personality traits and psychological abilities crucial for individuals' career development and serve as a fundamental foundation for maintaining overall well-being, particularly within clinical medical professions. Faced with significant work, academic, and doctor-patient communication pressures, medical students often encounter challenges to their mental and emotional health. Hence, the measurement, cultivation, and understanding of the relationship between medical students' professional psychological qualities and their mental health hold significant practical implications. Previous research has paid relatively little attention to the professional psychological qualities of medical student populations. Our study addressed this gap by developing a comprehensive professional psychological qualities scale through a series of qualitative and quantitative studies, comprising three main components and thirteen secondary dimensions. After multiple revisions and factor analyses, the total scale demonstrated a satisfactory α coefficient of 0.947, with Cronbach's α coefficients for the subscales of professional psychological traits, competences, and identity ranging from 0.895 to 0.933, meeting the basic requirements of scientific psychological research. Subsequently, using this scale, Study 2 explored the anxiety and depression levels of 972 medical students and conducted simple mediation analysis, revealing that medical students' professional psychological qualities directly negatively impact depression levels and indirectly positively influence them via their effects on anxiety levels, thereby exhibiting an overall masking effect unrelated to depression levels. Our study contributes by providing other researchers with a reliable measurement tool to assess medical students' professional psychological qualities while also shedding light on the complex mechanisms through which these qualities impact the mental health process.